PENGARUH KESEIMBANGAN KEHIDUPAN DAN PEKERJAAN, KONFLIK PEKERJAAN-KELUARGA DAN PEMOTONGAN UPAH TERHADAP KESEJAHTERAAN PSIKOLOGIS KARYAWAN DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING - Tyas Arum Sulistyorini (Jurnal Akuntansi dan Pajak, 2023)
The COVID-19 pandemic has brought changes in various aspects of life and one of them is in work. The existence of the COVID-19 pandemic has forced companies to take steps to minimize the risk of their employees contracting COVID-19 by implementing a work from home policy. The employee stated that while working from home he experienced pressure from two sides which caused an increase in stress among employees who worked from home considering that Instituion X had implemented this policy since March 2020. The purpose of this study was to determine the factors that increase psychological well-being. Institution X’s employees who work from home during the COVID-19 pandemic. This research is a case study where the source of the data obtained from the answers to the questionnaire by the research respondents. Work-life balance has a negative effect on work stress, work-family conflict and wage cuts have no effect on work stress, work-life balance has a positive effect on psychological well-being, work-family conflict and work stress negatively affect psychological well-being, wage cuts have no effect on psychological well-being. Keywords: work-life balance, work-family conflict, pay cuts, psychological well-being, work stress